Perception of elementary school students regarding an episode of hailstorm - Bortoluzzi, Leandro Neri (Geosaberes, 2019)
This work presents an experience of a school activity developed with students of elementary school II, in two classes of the sixth grade, of Gustavo Dobrandino da Silva State School, in the year of 2018. The students were between 10 and 14 years old. The objective was to analyze the students' perceptions regarding the extreme event of 07/09/2015, when an intense hailstorm occurred, causing great material destruction in the tri-border Brazil, Argentina and Paraguay. In this study, all the students participating in the activity were Brazilian and resident in the south of Foz do Iguaçu, state of Paraná. The applied questionnaire had ten multiple choice questions. As a result, it can be verified that even after three years, the event still lives in the collective and individual memory of all students, due to the intensity of the phenomenon and its destruction.